Theological hermeneutics - Jensen, Alexander S., 1968- (London, UK : SCM Press, 2007)
"Hermeneutics is the theory of understanding, which becomes relevant whenever understanding becomes problematic. Religious and other authoritative texts do not make sense any more, in a changing context, and so reflection on the way in which they are understood becomes necessary. The SCM Core Text: Theological Hermeneutics provides a historical outline of the problem of understanding from the beginnings to the present, focusing on key thinkers and their theological and philosophical contexts. It follows the development of hermeneutics from the theory of the interpretation of texts to that of the interpretation of existence. Following the hermeneutic school, it presents the hermeneutical problem as the foundational theological and philosophical question."--Jacket.
Introduction -- Hermeneutics in antiquity -- Augustine of Hippo -- The Middle Ages -- Humanism and the Reformation -- Rationalism and Enlightenment -- Friedrich Schleiermacher : Hermeneutics as the art of understanding -- Historicism -- Existentialism I : Martin Heidegger and Rudolf Bultmann -- Existentialism II : the path to language -- The universality of the sign I : open sign systems -- the universality of the sign II : closed sign systems -- Critical theory, feminism and postcolonialism -- Towards a hermeneutical theology -- Conclusion.
Formerly CIP.
Includes bibliographical references and indexes.
Keywords: Bible -- Hermeneutics -- History; Bible -- Criticism, interpretation, etc -- History; Bible; Hermeneutics -- Religious aspects -- Christianity; Criticism, interpretation, etc; History